Genome-informed investigation of the molecular evolution and genetic reassortment of severe fever with thrombocytopenia syndrome virus. - Kyuyoung Lee; Jong Hyeon Seok; Hyunbeen Kim; Sejik Park; Sohyun Lee; Joon-Yong Bae; Kyeongseok Jeon; Jun-Gu Kang; Jeong Rae Yoo; Sang Taek Heo; Nam-Hyuk Cho; Keun Hwa Lee; et al. (Public Library of Science (PLoS), 2023)
Background Severe fever with thrombocytopenia syndrome virus (SFTSV) is a viral pathogen causing significant clinical signs from mild fever with thrombocytopenia to severe hemorrhages. World Health Organization has paid special attention to the dramatic increase in human SFTS cases in China, Japan, and South Korea since the 2010s. The present study investigated the molecular evolution and genetic reassortment of SFTSVs using complete genomic sequences. Methods/principal finding We collected the complete genome sequences of SFTSVs globally isolated until 2019 (L segment, n = 307; M segment, n = 326; and S segment, n = 564) and evaluated the evolutionary profiles of SFTSVs based on phylogenetic and molecular selection pressure analyses. By employing a time-scaled Bayesian inference method, we found the geographical heterogeneity of dominant SFTSV genotypes in China, Japan, and South Korea around several centuries before and locally spread by tick-born spillover with infrequent long-distance transmission. Purifying selection predominated the molecular evolution of SFTSVs with limited gene reassortment and fixed substitution, but almost all three gene segments appeared to harbor at least one amino acid residue under positive selection. Specifically, the nonstructural protein and glycoprotein (Gn/Gc) genes were preferential selective targets, and the Gn region retained the highest number of positively selected residues. Conclusion/significance Here, the large-scale genomic analyses of SFTSVs improved prior knowledge of how this virus emerged and evolved in China, Japan, and South Korea. Our results highlight the importance of SFTSV surveillance in both human and non-human reservoirs at the molecular level to fight against fatal human infection with the virus.